Improved quasi‐physical zone division model with analytical electrothermal Ids model for AlGaN/GaN heterojunction high electron mobility transistors. (10th June 2019) - Chen, Yongbo; Xu, Yuehang; Wang, Feng; Wang, Changsi; Zhang, Yong; Yan, Bo; Xu, Ruimin
Abstract: An accurate analytical electrothermal drain current ( I ds ) model for AlGaN/GaN HEMTs is presented in this letter. The model is implemented into our recently proposed quasi‐physical zone division (QPZD) model for demonstration purpose. Compared with the original QPZD model, its electrothermal characteristics are enhanced by involving more fundamental temperature dependent elements. In addition, these elements are derived analytically based on physical mechanisms instead of former pure empirical fitting method. Thus, the extracted parameter values are more close to intrinsic values. An in house 0.15‐μm GaN HEMT is used for validation. Compared with the measured data at a wide ambient temperature range (245‐390 K), this electrothermal model demonstrates good accuracy to predict the DC characteristics and RF performances of GaN HEMTs.